Penggunaan Strategi Kooperatif Model Group Investigation Bagi Siswa yang Mengalami Attention Devicit Hyperactive Disorder (ADHD) - Nila Zaimatus Septiana; Chusnul Chuluq; Choiru Umatin Ummah (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2020)
This study aimed to discuss the importance of applying the cooperative Group Investigative model cooperative strategy for students who use ADHD specifically in class III-B MI Nizhamiyah Rejoagung, Ploso, Jombang. This study uses a qualitative method with a case study design that uses two cycles in its application. Taking the subject of this study using purposive sampling technique that is the subject that has the characteristics of ADHD sufferers. ADHD sufferers fail to overcome difficulties (inattention), self-control (impulsivity), and hyperactivity. After implementing a cooperative strategy, the model group investigations on these students using two phases, make conclusions about the first phase to successfully make ADHD sufferers focus on the task and reduce the risk of excessive.